Preparation method and application of modified phosphate antirust pigment
By controlling the molar ratio of amorphous silica, zinc oxide and phosphoric acid, modifying phosphate anti-rust pigments are prepared, which solves the problem of insufficient performance of zinc phosphate under the requirements of high corrosion resistance and achieves a more comprehensive corrosion resistance effect.
Patent Information
- Application Number
- CN202310314196.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-03-28
AI Technical Summary
Existing environmentally friendly anti-rust pigments such as zinc phosphate do not perform well in scenarios with high corrosion resistance requirements and cannot replace the performance of traditional heavy metal anti-rust pigments.
Modified phosphate anti-rust pigment is prepared by controlling the molar ratio of amorphous silica, zinc oxide and phosphoric acid within the range of (0.5-0.8): (2.8-3.2): (0.8-1.2), and using amorphous two The porous structure of silicon oxide and the complexing of zinc oxide improve corrosion resistance.
It significantly improves the corrosion resistance of modified phosphate anti-rust pigments, provides a more comprehensive protection effect, and is suitable for high-performance coatings and ink applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a preparation method and application of a modified phosphate anti-rust pigment. Background Art
[0002] Anti-corrosion coatings are an effective means of protecting metals and are widely used in various industrial fields. Anti-rust pigments, as a key component of anti-corrosion coatings, play a decisive role in their anti-corrosion effect. Therefore, the selection and optimization of anti-rust pigments are of great significance in terms of anti-corrosion performance and are also the development direction.
[0003] Traditional heavy metal anti-rust pigments (mainly chromium and lead) have excellent performance and are reasonably priced, and are widely used in paint formulations. However, the hazards of heavy metal anti-rust pigments have been clearly proven, and they can cause harm to the ecosystem and the human body. The national standard GB30981-2020 clearly restricts heavy metals in paints and stipulates an upper limit on the amount used. At present, with the control of environmental protection policies, domestic and foreign paint manufacturers are gradually phasing out such anti-rust pigments and developing environmentally friendly anti-rust pigments.
[0004] Zinc phosphate is a common environmentally friendly anti-rust pigment. Its eco-toxicity is significantly lower than that of heavy metals and its cost is not high. It is widely used in many coating formulations with low performance requirements. However, its low chemical activity and single anti-corrosion mechanism are far from the anti-corrosion performance of heavy metal anti-rust pigments, and it cannot meet the scenarios with high anti-corrosion performance requirements. Therefore, it is very meaningful to chemically modify zinc phosphate to further improve its anti-corrosion performance. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a preparation method and application of a modified phosphate anti-rust pigment with excellent anti-corrosion performance.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0008] Add amorphous silicon dioxide into water to prepare slurry, add zinc oxide into the slurry, and stir evenly;
[0009] Adding phosphoric acid aqueous solution to the slurry, stirring evenly, heating to 85-95° C., and keeping the temperature for 1-4 hours, washing, filtering, and drying to obtain a modified phosphate antirust pigment;
[0010] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is (0.5-0.8):(2.8-3.2):(0.8-1.2).
[0011] As a preferred embodiment of the present invention, the method for preparing amorphous silicon dioxide comprises the following steps:
[0012] (1) adding water to a reaction kettle, heating to 50-60° C., adjusting the pH to 1-4, adding water glass solution and sulfuric acid aqueous solution to the reaction kettle in parallel, reacting until a gel point appears, and continuing the reaction for 3-5 hours to form a gel block;
[0013] (2) Stirring and breaking the gel blocks, taking them out to obtain a mixed material, and washing them with hot water until the conductivity of the mixed material is 4000-6000 us / cm;
[0014] (3) Add the washed product to a reactor, add water, raise the temperature to 60-80° C., adjust the pH to 8-11, and age for 2-4 hours;
[0015] (4) filtering the aged material, washing with water until the conductivity of the material is less than 1000 us / cm, and drying to obtain amorphous silicon dioxide.
[0016] As a preferred embodiment of the present invention, the specific surface area of the amorphous silicon dioxide is 300 to 500 m 2 / g.
[0017] As a preferred embodiment of the present invention, the modulus of the water glass solution is 3.3, and the mass concentration of silicon dioxide in the water glass solution is 15-25%; and / or
[0018] The mass fraction of the aqueous sulfuric acid solution is 30-60%.
[0019] As a preferred embodiment of the present invention, the flow rate ratio of the water glass solution and the sulfuric acid aqueous solution is (3-4):1;
[0020] The flow rate of the water glass solution is 21-28 ml / min, and the flow rate of the sulfuric acid aqueous solution is 7 ml / min.
[0021] As a preferred embodiment of the present invention, the temperature of the hot water is 50-80°C; and / or
[0022] In step (3), the mass ratio of the washed product to water is 1:(2-6).
[0023] As a preferred embodiment of the present invention, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0024] As a preferred embodiment of the present invention, the content of amorphous silicon dioxide in the slurry is 20 to 35 wt %.
[0025] As a preferred embodiment of the present invention, the mass fraction of the phosphoric acid aqueous solution is 10-20%.
[0026] The present invention also provides the use of the modified phosphate antirust pigment prepared by the above-mentioned preparation method in coatings and inks.
[0027] The beneficial effects of the present invention are: (1) the preparation method of the modified phosphate anti-rust pigment of the present invention comprises three key raw materials: amorphous silicon dioxide, zinc oxide and phosphoric acid, and a modified phosphate anti-rust pigment with excellent anti-corrosion performance is prepared; (2) the present invention can effectively improve the anti-corrosion performance of the modified phosphate anti-rust pigment by controlling the molar ratio of the three within the range of (0.5-0.8): (2.8-3.2): (0.8-1.2); (3) the amorphous silicon dioxide synthesized by the present invention is the key to improving the anti-corrosion performance, which is obtained by sol-gel, has a porous structure inside and has a high porosity. The structure can have a high specific surface area. On the one hand, it can adsorb corrosive ions. On the other hand, it can adsorb phosphate on its surface, increasing the area of phosphate contacting the environment for hydrolysis, thereby indirectly increasing the hydrolysis activity of phosphate, and further effectively improving the anti-corrosion performance. (4) The amorphous silicon dioxide and zinc oxide prepared by the present invention have a significant synergistic effect in improving the anti-corrosion performance. Among them, the amorphous silicon dioxide has a relatively fast adsorption or hydrolysis rate, which mainly plays a role in the early and middle stage corrosion protection of the coating. It adsorbs phosphate on its surface, increasing the area of phosphate contacting the environment for hydrolysis, thereby indirectly increasing the hydrolysis activity of phosphate, and can react with the substrate to form a silicate passivation film. Zinc oxide can form a complex with phosphoric acid, but the hydrolysis rate is slow (amorphous silicon dioxide can increase the hydrolysis activity of phosphate), which helps the mid- and late stage corrosion protection of the coating. The two interact with each other to provide a more comprehensive anti-corrosion effect. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0030] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0032] In the present invention, unless otherwise stated, all parts are parts by mass.
[0033] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0034] The embodiment of the present invention provides a method for preparing a modified phosphate antirust pigment, comprising the following steps:
[0035] Add amorphous silicon dioxide into water to prepare slurry, add zinc oxide into the slurry, and stir evenly;
[0036] Add phosphoric acid aqueous solution to the slurry, stir evenly, heat to 85-95° C., and keep warm for 1-4 hours, wash, filter, and dry to obtain a modified phosphate anti-rust pigment.
[0037] The preparation method of the modified phosphate anti-rust pigment of the present invention comprises three key raw materials: amorphous silicon dioxide, zinc oxide and phosphoric acid, and the modified phosphate anti-rust pigment with excellent anti-corrosion performance is prepared.
[0038] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is (0.5-0.8):(2.8-3.2):(0.8-1.2).
[0039] The inventors of the present invention have found through extensive research that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is the key to affecting the performance. By controlling the molar ratio of the three within the range of (0.5-0.8): (2.8-3.2): (0.8-1.2), the anti-corrosion performance of the modified phosphate anti-rust pigment can be effectively improved.
[0040] The inventors explored the effects of the single molar ratio of the above three on the performance and found that:
[0041] If the molar ratio of amorphous silica is too low, that is, lower than 0.5, the wet adhesion will decrease, blistering will occur easily, and the anti-corrosion performance will decrease significantly. If the molar ratio of amorphous silica is too high, that is, higher than 1, the anti-corrosion performance will decrease significantly, especially the anti-rust performance will decrease significantly.
[0042] If the molar ratio of zinc oxide is too low, that is, lower than 2.8, the rust level will increase significantly. If the molar ratio of zinc oxide is too high, that is, higher than 3.2, it will cause bubbles to form easily, thereby reducing the anti-corrosion performance.
[0043] If the molar ratio of phosphoric acid is too low, that is, lower than 0.8, not only will the rust level increase significantly, but it will also be very easy to bubble; if the molar ratio of phosphoric acid is too high, that is, higher than 1.2, it will cause a significant increase in the rust level and it will also be very easy to bubble, thereby reducing the anti-corrosion performance.
[0044] Therefore, the molar ratio of the three needs to be strictly controlled in the present invention.
[0045] It should be noted that regarding the explanation of the molar ratio of the three, for example, when the molar ratio of amorphous silica, zinc oxide and phosphoric acid is 0.6:3:1, for every 0.6 mol of amorphous silica added, 3 mol of zinc oxide and 1 mol of phosphoric acid need to be added.
[0046] Here, phosphoric acid refers to phosphoric acid contained in a phosphoric acid aqueous solution.
[0047] In one embodiment, the method for preparing amorphous silicon dioxide comprises the following steps:
[0048] (1) adding water to a reactor, raising the temperature to 50-60° C., adjusting the pH to 1-4 (the pH can be adjusted by a phosphoric acid aqueous solution during the process), adding a water glass solution and a sulfuric acid aqueous solution to the reactor in parallel to react, and reacting until a gel point appears, continuing the reaction for 3-5 hours to form a gel block;
[0049] (2) Stirring and breaking the gel blocks, taking them out to obtain a mixed material, and washing them with hot water until the conductivity of the mixed material is 4000-6000 us / cm;
[0050] (3) Add the washed product to a reactor, add water, raise the temperature to 60-80° C., adjust the pH to 8-11 (the pH is adjusted by sodium hydroxide solution in this process), and age for 2-4 hours;
[0051] (4) filtering the aged material, washing with water until the conductivity of the material is less than 1000 us / cm, and drying to obtain amorphous silicon dioxide.
[0052] The amorphous silicon dioxide synthesized by the present invention is the key to improving the anti-corrosion performance. It is obtained by sol-gel, and the internal structure is a porous structure with a high porosity. The structure can have a high specific surface area, which can adsorb corrosive ions on the one hand, and adsorb phosphate on its surface on the other hand, thereby increasing the area of phosphate contacting the environment for hydrolysis, thereby indirectly increasing the hydrolysis activity of phosphate radicals, and then effectively improving the anti-corrosion performance.
[0053] At the same time, the inventors of the present invention have found that the performance of the amorphous silicon dioxide prepared by the present invention is significantly better than that of crystalline silicon dioxide. The internal structure of crystalline silicon dioxide is dense, completely insoluble in water, and cannot participate in the establishment of a protective film.
[0054] The inventors of the present invention have found that the amorphous silicon dioxide and zinc oxide prepared by the present invention have a significant synergistic effect in improving the corrosion resistance. Among them, the adsorption or hydrolysis rate of amorphous silicon dioxide is relatively fast, which mainly plays a role in the early and middle stage corrosion resistance of the coating. Phosphate is adsorbed on its surface, which increases the area of phosphate contact with the environment for hydrolysis, thereby indirectly improving the hydrolysis activity of phosphate, and can react with the substrate to form a silicate passivation film. Zinc oxide can form a complex with phosphoric acid, but the hydrolysis rate is slow (amorphous silicon dioxide can increase the hydrolysis activity of phosphate), which helps the mid- and late stage corrosion resistance of the coating. The two interact with each other to provide a more comprehensive corrosion resistance effect.
[0055] Determination of gel point: Gel point is an accurate term in the art, and those skilled in the art know how to determine when the gel point occurs; the gel point is the critical reaction degree at the moment when gel begins to appear.
[0056] As a preferred embodiment of the present invention, the specific surface area of the amorphous silicon dioxide is 300 to 500 m 2 / g.
[0057] The specific surface area of the amorphous silicon dioxide prepared by the above method is 300 to 500 m 2 / g, where the specific surface area is measured using a BET tester of 3H-2000PS2. If the specific surface area is too low, the contact area with zinc phosphate is low, resulting in fewer adsorption sites, which affects the anti-corrosion activity of the material. If the specific surface area is too high, the contact area with zinc phosphate is large, resulting in more adsorption sites. In the anti-corrosion process, the active components are released too quickly, resulting in insufficient anti-corrosion performance in the later stage.
[0058] In one embodiment, the modulus of the water glass solution is 3.3, and the mass concentration of silicon dioxide in the water glass solution is 15-25%; and / or
[0059] The mass fraction of the aqueous sulfuric acid solution is 30-60%.
[0060] In one embodiment, the flow rate ratio of the water glass solution and the sulfuric acid aqueous solution is (3-4):1;
[0061] The flow rate of the water glass solution is 21-28 ml / min, and the flow rate of the sulfuric acid aqueous solution is 7 ml / min.
[0062] In one embodiment, the temperature of the hot water is 50-80° C.; and / or
[0063] In step (3), the mass ratio of the washed product to water is 1:(2-6).
[0064] In one embodiment, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0065] In one embodiment, the content of amorphous silica in the slurry is 20-35wt%. The preparation of the slurry is exemplified by taking the molar ratio of amorphous silica, zinc oxide and phosphoric acid as 0.6:3:1. At this time, for every 0.6 mol of amorphous silica added, 3 mol of zinc oxide and 1 mol of phosphoric acid are required. The mass of 0.6 mol of amorphous silica is 0.6*60.08 g. At this time, the mass of silica is clear, and only water needs to be added to dilute it to the specified concentration.
[0066] In one embodiment, the mass fraction of the phosphoric acid aqueous solution is 10-20%.
[0067] The preparation of phosphoric acid solution is illustrated by taking the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid as 0.6:3:1. At this time, for every 0.6 mol of amorphous silicon dioxide added, 3 mol of zinc oxide and 1 mol of phosphoric acid need to be added. The mass of 1 mol is 1*98g. It only needs to be diluted with water to the specified concentration.
[0068] One embodiment of the present invention provides the use of the modified phosphate anti-rust pigment prepared by the above-mentioned preparation method in coatings and inks.
[0069] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.
[0070] Example 1
[0071] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0072] (1) preparing a water glass solution with a silica concentration of 23 wt %, a modulus of 3.3, and a sulfuric acid aqueous solution with a mass fraction of 45%;
[0073] (2) adding 1 / 5 of the reactor volume of water to the reactor, turning on the stirrer at a stirring speed of 400 rpm, raising the temperature to 55° C., and adjusting the pH to 3 with a sulfuric acid aqueous solution;
[0074] (3) adjusting the speed of the stirrer to 900 rpm, and adding the water glass solution at a flow rate of 25 mL / min and the sulfuric acid aqueous solution at a flow rate of 7 mL / min to the reactor in parallel for 1 h to react until the gel point appears, and continuing the reaction for 3 h to form a gel block;
[0075] (4) adjusting the speed of the stirrer to 1200 rpm, breaking the gel blocks, taking them out, obtaining a mixed material body, and washing the mixed material body with hot water at 60° C. until the conductivity reaches 5000 us / cm;
[0076] (5) The washed product was added to a reactor, three times the mass of water was added, the temperature was raised to 70°C, the pH was adjusted to 10 with a 20% mass fraction of sodium hydroxide solution, aged for 3 hours, filtered, washed with pure water until the conductivity was less than 1000us / cm, and dried to obtain porous amorphous silica. The BET specific surface area of the amorphous silica was 401m 2 / g;
[0077] (6) adding water to the reaction kettle, adjusting the speed of the stirrer to 400 rpm, and adding the amorphous silicon dioxide prepared in step (5) and water to prepare a slurry with a mass fraction of 25%;
[0078] (7) Add zinc oxide, stir until the pH is stable, and continue stirring for 30 minutes;
[0079] (8) adding a 15% by mass phosphoric acid aqueous solution, stirring for 1 hour, heating to 90° C., aging for 2 hours, washing, filtering, and drying the product to obtain a modified phosphate antirust pigment.
[0080] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0081] Example 2
[0082] The difference between Example 2 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0083] In this embodiment, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.5:2.8:0.8.
[0084] Example 3
[0085] The difference between Example 3 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0086] In this embodiment, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.5:3.2:1.2.
[0087] Example 4
[0088] The difference between Example 4 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0089] In this embodiment, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.8:2.8:0.8.
[0090] Example 5
[0091] The difference between Example 5 and Example 1 is that the water glass solution is different, resulting in the BET specific surface area of amorphous silicon dioxide being 495 m 2 / g, everything else is the same.
[0092] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0093] (1) preparing a water glass solution with a silica concentration of 15 wt %, a modulus of 3.3, and a sulfuric acid aqueous solution with a mass fraction of 45%;
[0094] (2) adding 1 / 5 of the reactor volume of water to the reactor, turning on the stirrer at a stirring speed of 400 rpm, raising the temperature to 55° C., and adjusting the pH to 3 with a sulfuric acid aqueous solution;
[0095] (3) adjusting the speed of the stirrer to 900 rpm, and adding the water glass solution at a flow rate of 25 mL / min and the sulfuric acid aqueous solution at a flow rate of 7 mL / min to the reactor in parallel for 1 h to react until the gel point appears, and continuing the reaction for 3 h to form a gel block;
[0096] (4) adjusting the speed of the stirrer to 1200 rpm, breaking the gel blocks, taking them out, obtaining a mixed material body, and washing the mixed material body with hot water at 60° C. until the conductivity reaches 5000 us / cm;
[0097] (5) The washed product was added to a reactor, three times the mass of water was added, the temperature was raised to 70°C, the pH was adjusted to 10 with a 20% sodium hydroxide solution, aged for 3 hours, filtered, washed with pure water until the conductivity was less than 1000us / cm, and dried to obtain porous amorphous silica. The BET specific surface area of the amorphous silica was 495m 2 / g;
[0098] (6) adding water to the reaction kettle, adjusting the speed of the stirrer to 400 rpm, and adding the amorphous silicon dioxide prepared in step (5) and water to prepare a slurry with a mass fraction of 25%;
[0099] (7) Add zinc oxide, stir until the pH is stable, and continue stirring for 30 minutes;
[0100] (8) adding a 15% by mass phosphoric acid aqueous solution, stirring for 1 hour, heating to 90° C., aging for 2 hours, washing, filtering, and drying the product to obtain a modified phosphate antirust pigment.
[0101] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0102] Example 6
[0103] The difference between Example 6 and Example 1 is that the concentration of the sulfuric acid aqueous solution is different, resulting in the BET specific surface area of the amorphous silicon dioxide being 314 m 2 / g, everything else is the same.
[0104] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0105] (1) preparing a water glass solution with a silica concentration of 23 wt %, a modulus of 3.3, and a sulfuric acid aqueous solution with a mass fraction of 30%;
[0106] (2) adding 1 / 5 of the reactor volume of water to the reactor, turning on the stirrer at a stirring speed of 400 rpm, raising the temperature to 55° C., and adjusting the pH to 3 with a sulfuric acid aqueous solution;
[0107] (3) adjusting the speed of the stirrer to 900 rpm, and adding the water glass solution at a flow rate of 25 mL / min and the sulfuric acid aqueous solution at a flow rate of 7 mL / min to the reactor in parallel for 1 h to react until the gel point appears, and continuing the reaction for 3 h to form a gel block;
[0108] (4) adjusting the speed of the stirrer to 1200 rpm, breaking the gel blocks, taking them out, obtaining a mixed material body, and washing the mixed material body with hot water at 60° C. until the conductivity reaches 5000 us / cm;
[0109] (5) The washed product was added to a reactor, three times the mass of water was added, the temperature was raised to 70°C, the pH was adjusted to 10 with a 20% sodium hydroxide solution, aged for 3 hours, filtered, washed with pure water until the conductivity was less than 1000 us / cm, and dried to obtain porous amorphous silica. The BET specific surface area of the amorphous silica was 314 m2 / g;
[0110] (6) adding water to the reaction kettle, adjusting the speed of the stirrer to 400 rpm, and adding the amorphous silicon dioxide prepared in step (5) and water to prepare a slurry with a mass fraction of 25%;
[0111] (7) Add zinc oxide, stir until the pH is stable, and continue stirring for 30 minutes;
[0112] (8) adding a 15% by mass phosphoric acid aqueous solution, stirring for 1 hour, heating to 90° C., aging for 2 hours, washing, filtering, and drying the product to obtain a modified phosphate antirust pigment.
[0113] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0114] Comparative Example 1
[0115] The difference between Comparative Example 1 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0116] In this comparative example, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.3:3:1.
[0117] Comparative Example 2
[0118] The difference between Comparative Example 2 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0119] In this comparative example, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 1.0:3:1.
[0120] Comparative Example 3
[0121] The difference between Comparative Example 3 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0122] In this comparative example, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:2.5:1.
[0123] Comparative Example 4
[0124] The difference between Comparative Example 4 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0125] In this comparative example, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3.5:1.
[0126] Comparative Example 5
[0127] The difference between Comparative Example 5 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0128] In this comparative example, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:0.6.
[0129] Comparative Example 6
[0130] The difference between Comparative Example 6 and Example 1 is that the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is different, and the others are the same.
[0131] In this comparative example, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.4.
[0132] Comparative Example 7
[0133] The difference between Comparative Example 7 and Example 1 is that amorphous silicon dioxide is not added in Comparative Example 7, and the other aspects are the same.
[0134] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0135] (1) Add zinc oxide to a phosphoric acid aqueous solution, stir for 1 hour, heat to 90° C., age for 2 hours, wash, filter, and dry the product to obtain a modified phosphate antirust pigment.
[0136] Among them, the molar ratio of zinc oxide to phosphoric acid is 3.6:1.
[0137] Comparative Example 8
[0138] The difference between Comparative Example 8 and Example 1 is that zinc oxide is not added in Comparative Example 8, and the other aspects are the same.
[0139] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0140] (1) preparing a water glass solution with a silica concentration of 23 wt %, a modulus of 3.3, and a sulfuric acid aqueous solution with a mass fraction of 45%;
[0141] (2) adding 1 / 5 of the reactor volume of water to the reactor, turning on the stirrer at a stirring speed of 400 rpm, raising the temperature to 55° C., and adjusting the pH to 3 with a sulfuric acid aqueous solution;
[0142] (3) adjusting the speed of the stirrer to 900 rpm, and adding the water glass solution at a flow rate of 25 mL / min and the sulfuric acid aqueous solution at a flow rate of 7 mL / min to the reactor in parallel for 1 h to react until the gel point appears, and continuing the reaction for 3 h to form a gel block;
[0143] (4) adjusting the speed of the stirrer to 1200 rpm, breaking the gel blocks, taking them out, obtaining a mixed material body, and washing the mixed material body with hot water at 60° C. until the conductivity reaches 5000 us / cm;
[0144] (5) The washed product was added to a reactor, three times the mass of water was added, the temperature was raised to 70°C, the pH was adjusted to 10 with a 20% mass fraction of sodium hydroxide solution, aged for 3 hours, filtered, washed with pure water until the conductivity was less than 1000us / cm, and dried to obtain porous amorphous silica. The BET specific surface area of the amorphous silica was 401m 2 / g;
[0145] (6) adding water to the reaction kettle, adjusting the speed of the stirrer to 400 rpm, and adding the amorphous silicon dioxide prepared in step (5) and water to prepare a slurry with a mass fraction of 25%;
[0146] (7) adding a 15% by mass phosphoric acid aqueous solution, stirring for 1 hour, heating to 90° C., aging for 2 hours, washing, filtering, and drying the product to obtain a modified phosphate antirust pigment.
[0147] The molar ratio of amorphous silicon dioxide to phosphoric acid is 3.6:1.
[0148] Comparative Example 9
[0149] Comparative Example 9 is amorphous silicon dioxide, and its preparation method is the same as that of Example 1.
[0150] Comparative Example 10
[0151] Comparative Example 10 is single zinc oxide.
[0152] Comparative Example 11
[0153] Comparative Example 11 is different from Example 1 in that the flow rate ratio of water glass to sulfuric acid is 5:1, which results in a BET specific surface area of amorphous silicon dioxide of 150 m 2 / g, everything else is the same.
[0154] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0155] (1) preparing a water glass solution with a silica concentration of 23 wt %, a modulus of 3.3, and a sulfuric acid aqueous solution with a mass fraction of 45%;
[0156] (2) adding 1 / 5 of the reactor volume of water to the reactor, turning on the stirrer at a stirring speed of 400 rpm, raising the temperature to 55° C., and adjusting the pH to 3 with a sulfuric acid aqueous solution;
[0157] (3) adjusting the speed of the stirrer to 900 rpm, and adding the water glass solution at a flow rate of 35 L / min and the sulfuric acid aqueous solution at a flow rate of 7 mL / min to the reactor in parallel for 1 h to react until the gel point appears, and continuing the reaction for 3 h to form a gel block;
[0158] (4) adjusting the speed of the stirrer to 1200 rpm, breaking the gel blocks, taking them out, obtaining a mixed material body, and washing the mixed material body with hot water at 60° C. until the conductivity reaches 5000 us / cm;
[0159] (5) The washed product was added to a reactor, three times the mass of water was added, the temperature was raised to 70°C, the pH was adjusted to 10 with a 20% mass fraction of sodium hydroxide solution, aged for 3 hours, filtered, washed with pure water until the conductivity was less than 1000us / cm, and dried to obtain porous amorphous silica. The BET specific surface area of the amorphous silica was 150m 2 / g;
[0160] (6) adding water to the reaction kettle, adjusting the speed of the stirrer to 400 rpm, and adding the amorphous silicon dioxide prepared in step (5) and water to prepare a slurry with a mass fraction of 25%;
[0161] (7) Add zinc oxide, stir until the pH is stable, and continue stirring for 30 minutes;
[0162] (8) adding a 15% by mass phosphoric acid aqueous solution, stirring for 1 hour, heating to 90° C., aging for 2 hours, washing, filtering, and drying the product to obtain a modified phosphate antirust pigment.
[0163] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0164] Comparative Example 12
[0165] The difference between Comparative Example 12 and Example 1 is that the reaction temperature is 25°C, which results in the BET specific surface area of amorphous silicon dioxide being 650 m 2 / g, everything else is the same.
[0166] A method for preparing a modified phosphate antirust pigment comprises the following steps:
[0167] (1) preparing a water glass solution with a silica concentration of 23 wt %, a modulus of 3.3, and a sulfuric acid aqueous solution with a mass fraction of 45%;
[0168] (2) adding 1 / 5 of the reactor volume of water to the reactor, turning on the stirrer at a stirring speed of 400 rpm, adjusting the temperature to 25° C., and adjusting the pH to 3 with a sulfuric acid aqueous solution;
[0169] (3) adjusting the speed of the stirrer to 900 rpm, and adding the water glass solution at a flow rate of 25 mL / min and the sulfuric acid aqueous solution at a flow rate of 7 mL / min to the reactor in parallel for 1 h to react until the gel point appears, and continuing the reaction for 3 h to form a gel block;
[0170] (4) adjusting the speed of the stirrer to 1200 rpm, breaking the gel blocks, taking them out, obtaining a mixed material body, and washing the mixed material body with hot water at 60° C. until the conductivity reaches 5000 us / cm;
[0171] (5) The washed product was added to a reactor, three times the mass of water was added, the temperature was raised to 70°C, the pH was adjusted to 10 with a 20% sodium hydroxide solution, aged for 3 hours, filtered, washed with pure water until the conductivity was less than 1000 us / cm, and dried to obtain porous amorphous silica. The BET specific surface area of the amorphous silica was 650 m 2 / g;
[0172] (6) adding water to the reaction kettle, adjusting the speed of the stirrer to 400 rpm, and adding the amorphous silicon dioxide prepared in step (5) and water to prepare a slurry with a mass fraction of 25%;
[0173] (7) Add zinc oxide, stir until the pH is stable, and continue stirring for 30 minutes;
[0174] (8) adding a 15% by mass phosphoric acid aqueous solution, stirring for 1 hour, heating to 90° C., aging for 2 hours, washing, filtering, and drying the product to obtain a modified phosphate antirust pigment.
[0175] The molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1.
[0176] Comparative Example 13
[0177] Comparative Example 13 is zinc phosphate, purchased from SNCZ, France.
[0178] Comparative Example 14
[0179] Comparative Example 14 is zinc polyphosphate, purchased from Hangzhou Haibo Antirust Pigment.
[0180] Test Case
[0181] 1. 5 parts by mass of the products of Examples 1 to 6 and Comparative Examples 1 to 14 (wherein, Examples 1 to 6, Comparative Examples 1 to 8, 11 to 12 are the corresponding anti-rust pigments, Comparative Example 9 is amorphous silicon dioxide, Comparative Example 10 is zinc oxide, Comparative Example 13 is zinc phosphate, and Comparative Example 14 is zinc polyphosphate) are respectively formulated with the substances in Table 1 to prepare water-based epoxy ester primers.
[0182] Table 1
[0183]
[0184]
[0185] 2. The anti-corrosion performance test of the coating refers to the ASTM B117 standard, the rust grade refers to the ASTM D610 standard, the blister grade refers to the ASTM D714 standard, and the pull-off adhesion test standard is GB / T 5210; the rust grade and blister grade results are 0 for the best and 10 for the worst. The test results are shown in Table 2.
[0186] Table 2
[0187]
[0188]
[0189] It can be seen from Examples 1-6 that the overall corrosion level is good, not exceeding level 2. In addition, the decrease in pull-off adhesion before and after the test is not obvious, not exceeding 27%. Among them, Example 1 is the best embodiment of the present invention and has the best anti-corrosion performance.
[0190] By comparing Example 1 with Comparative Examples 1 to 6, it can be seen that in the present invention, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid needs to be strictly controlled. The excellent anti-corrosion performance of the anti-rust pigment of the present invention is achieved under the joint action of the three. Controlling the molar ratio of the three within the scope of the present invention can effectively improve the anti-corrosion performance. If the molar ratio of the three deviates slightly from the scope of the present invention, the anti-corrosion performance will be significantly reduced.
[0191] By comparing Example 1 with Comparative Examples 1 to 2, it can be seen that as the amount of amorphous silica added decreases, the blistering in the salt spray test becomes more severe, from level 1 to level 6, and the pull-off adhesion also decreases significantly by more than 50%, which indicates that amorphous silica can significantly improve the wet adhesion of the paint film, thereby enhancing the anti-blistering ability; if the amount of amorphous silica added is too high, the rust level will be significantly increased to level 5.
[0192] Comparing Example 1 with Comparative Examples 3-4, it can be seen that as the zinc oxide content decreases, the rust level increases significantly to level 7. This shows that zinc oxide is helpful for scribe corrosion. However, when the zinc oxide content is too high, the blistering level is more serious, reaching level 7.
[0193] By comparing the embodiment with comparative examples 5 to 6, it can be seen that too high or too low a content of phosphoric acid will affect the anti-corrosion performance.
[0194] By comparing Example 1 with Comparative Examples 7 to 10, it can be seen that the anti-corrosion performance of using amorphous silicon dioxide or zinc oxide alone or not adding amorphous silicon dioxide or zinc oxide in the preparation process is obviously inferior to that of Example 1, which also shows that there is a synergistic effect between the two in the anti-corrosion mechanism process. The relative speed of silicon dioxide adsorption or hydrolysis is relatively fast, which mainly plays a role in the early and middle stage anti-corrosion of the coating. Zinc oxide can form a complex with phosphoric acid, but the hydrolysis rate is slow, which helps the mid-to-late stage anti-corrosion performance of the coating. The two interact with each other to provide a more comprehensive anti-corrosion effect.
[0195] Comparison of Example 1 with Comparative Examples 11 and 12 shows that the specific surface area of amorphous silicon dioxide is not between 300 and 500 m 2 / g, and its anti-corrosion performance is not as good as that of Example 1. The amorphous silicon dioxide used in Comparative Example 11 has a lower specific surface area (150m 2 / g), the contact area with zinc phosphate is low, resulting in fewer adsorption sites, which affects the anti-corrosion activity of the material. The amorphous silica used in ratio 12 has a high specific surface area (650m 2 / g), which has a large contact area with zinc phosphate and many adsorption sites. In the anti-corrosion process, the active components are released too quickly, resulting in insufficient anti-corrosion performance in the later stage. Therefore, it is necessary to control the specific surface area of amorphous silica to 300-500m 2 / g.
[0196] Comparative Examples 13 and 14 are both common commercial products, and their anti-corrosion performance is significantly worse than that of the modified phosphate anti-rust pigment prepared by the present invention.
[0197] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified phosphate anti-rust pigment, characterized in that: The following steps are involved: Add amorphous silicon dioxide into water to prepare slurry, add zinc oxide into the slurry, and stir evenly; Adding phosphoric acid aqueous solution to the slurry, stirring evenly, heating to 85-95° C., and keeping the temperature for 1-4 hours, washing, filtering, and drying to obtain a modified phosphate antirust pigment; Wherein, the molar ratio of amorphous silicon dioxide, zinc oxide and phosphoric acid is 0.6:3:1, 0.5:2.8:0.8, 0.8:3.2:1.2 or 0.8:2.8:0.8; The preparation method of the amorphous silicon dioxide comprises the following steps: (1) adding water to a reaction kettle, heating to 50-60° C., adjusting the pH to 1-4, adding water glass solution and sulfuric acid aqueous solution to the reaction kettle in parallel, reacting until a gel point appears, and continuing the reaction for 3-5 hours to form a gel block; (2) Stirring and breaking the gel blocks, taking them out to obtain a mixed material, and washing them with hot water until the conductivity of the mixed material is 4000-6000 us / cm; (3) Add the washed product to a reactor, add water, raise the temperature to 60-80° C., adjust the pH to 8-11, and age for 2-4 hours; (4) filtering the aged material, washing with water until the conductivity of the material is less than 1000 us / cm, and drying to obtain amorphous silicon dioxide; The specific surface area of the amorphous silicon dioxide is 300 to 500 m 2 / g.
2. The method for preparing the modified phosphate antirust pigment according to claim 1, characterized in that: The modulus of the water glass solution is 3.3, and the mass concentration of silicon dioxide in the water glass solution is 15-25%; and / or The mass fraction of the aqueous sulfuric acid solution is 30-60%.
3. The method for preparing the modified phosphate antirust pigment according to claim 1, characterized in that: The flow rate ratio of the water glass solution and the sulfuric acid aqueous solution is (3-4):1; The flow rate of the water glass solution is 21-28 ml / min, and the flow rate of the sulfuric acid aqueous solution is 7 ml / min.
4. The method for preparing the modified phosphate antirust pigment according to claim 1, characterized in that: The temperature of the hot water is 50-80°C; and / or In step (3), the mass ratio of the washed product to water is 1:(2-6).
5. The method for preparing the modified phosphate antirust pigment according to claim 1, characterized in that: The content of amorphous silicon dioxide in the slurry is 20-35 wt %.
6. The method for preparing the modified phosphate antirust pigment according to claim 1, characterized in that: The mass fraction of the phosphoric acid aqueous solution is 10-20%.
7. Use of the modified phosphate antirust pigment prepared by the preparation method according to any one of claims 1 to 6 in coatings and inks.
